Deskripsi Pembelajaran di Pondok Pesantren Putri - Rohmatul Kholidah (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
This article intends to describe the learning Marasah Diniyah daughter (Madin), Assembly Musyawatah Madrasah (M2M), and Tartil Quran (TQ). The approach used in this paper is a descriptive qualitative research. Data collection techniques of documentation, observation, and interviews. As for the author uses analysis techniques to analyze data reduction, data presentation, and data verification. The results of the study, pembalajaran in Madin, M2M TQ of Kediri greatly influenced by the role diligence of the teachers in teaching and learning activities in the classroom, as well as the readiness of the students, habituation sets student discipline, and set the method of punishment